SIMBOLISME DALAM TRADISI LISAN PASANG RI KAJANG: TINJAUAN SEMIOTIK - Basrah Gising (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Semiotics  is a set of analysis  that has been applied in linguistics  and anthropology.  This  article  is  focused  on  language  and  cultural  symbols  that  are stated in pasang ri Kajang and will be analyzed based on grand theory of semantics.This research used a qualitative research perspective. The validity of data is examined by collecting the data collecting through interview, recording, taking note, elicitation and Focus Group Study. The result of the research indicates that Pasang ri Kajang contains a holy ancestor messages that has been transferred in oral tradition. These messages contain some local wisdoms of sustainable environmental management.  The topic of this research is local knowledge  system that concerns with hydraulic cycle system that is stated in some matters of pasang ri Kajang. The relationship between the matters build a substantial concept that concerns with hydraulic cycle system in ecology.